Imatinib mesylate in combination with pembrolizumab in patients with advanced KIT-mutant melanoma following progression on standard therapy: A phase I/II trial and study protocol. Issue 49 (10th December 2021) - Hirai, Ikuko; Tanese, Keiji; Fukuda, Keitaro; Fusumae, Takayuki; Nakamura, Yoshio; Sato, Yasunori; Amagai, Masayuki; Funakoshi, Takeru
Abstract: Introduction: Genetic alterations of KIT gene are known to be one of the major causes of melanoma. Those are more common in the mucous and acral subtypes and KIT is regarded as major oncogene in Asian melanomas, where the prevalence of these subtypes is high. Up to date, several clinical trials have been conducted to target KIT gene alterations in melanoma with unsatisfied efficacies. Imatinib mesylate, a small-molecule inhibitor of the KIT tyrosine kinase, provides a rapid but not durable clinical response in KIT -mutant melanoma. Meanwhile, recent basic and clinical evidence have revealed another aspect of KIT-targeted therapy, namely the enhancement of antitumor activity of immune checkpoint inhibitors. Herein, we designed clinical trial of co-administrating imatinib mesylate and pembrolizumab (anti-PD-1 antibody) to evaluate its safety and efficacy. Methods and analysis: This is an open-label, single-arm, phase I/II clinical trial involving Japanese patients with metastatic KIT -mutant melanoma that are refractory to standard therapy including anti-PD-1 therapy. Phase I study is a dose-escalation study comprising two dose levels of imatinib mesylate (200 and 400 mg/day, respectively) with fixed dose of pembrolizumab (200 mg every 3 weeks) to evaluate safety and tolerability and determine recommended phase II dose. The primary endpoint of the phase II study is the objective response rate after 4 cycles (3 weeks/cycle) of pembrolizumab and imatinib mesylate at the dose determined in phase I, based on RECIST version 1.1. A Simon's minimax two-stage design is employed to test the null hypothesis of a 5% response rate vs 30% alternative, which will be rejected when a lower confidence limit of two-sided 90% confidence interval of true response rate is over than threshold response rate. The secondary endpoints include progression free survival, overall survival, best overall response and incidence of adverse events. Totally, a target size of 22 patients will be expected. Discussion: If this study shows efficacy and acceptable safety profile, it will contribute to the development of novel treatment option for patients with KIT -mutant melanoma that are refractory to standard therapy. Trial registration: NCT04546074. Date of Registration: September 11, 2020 (https://clinicaltrials.gov/ct2/show/NCT04546074 ). Date of First Participant Enrollment: December 23, 2020.